A comprehensive review of factors influencing the sound absorption properties of micro-perforated panel structures - Mohammadi, Majid; Ishak, Mohamad Ridzwan; Sultan, Mohamed Thariq Hameed; Zainudin, Edi Syams (Springer, 2025)
This review provides an in-depth analysis of the key factors influencing the sound absorption properties of micro-perforated panel structures, with a particular emphasis on their effectiveness in low-frequency acoustic applications. Low-frequency noise control remains a critical challenge in a variety of industries, and MPPs are increasingly recognized for their potential to address this issue due to their ability to provide efficient sound attenuation across a broad frequency range. The paper begins by highlighting the growing importance of sound absorbers, particularly those based on natural fiber-reinforced composites, which offer an environmentally sustainable alternative to traditional materials. The review then delves into the key design parameters that affect MPP performance, including perforation diameter, perforation ratio, panel thickness, cavity depth, and the material properties of the panel itself. Each of these factors is critically examined in terms of its impact on the acoustic behavior of MPPs. Furthermore, the latest research advancements in the field are discussed, including innovative approaches to optimizing MPP configurations and enhancing their sound absorption efficiency. This review highlighted that optimizing MPPs for sound absorption requires precise control over MPP’s parameters so that smaller perforations enhance high-frequency absorption, while larger ones expand the effective range. The perforation ratio influences airflow resistance and energy dissipation, impacting both high- and low-frequency performance. Panel thickness and air gap depth affect resonance and impedance matching. Additionally, sustainable materials like natural fiber composites improve damping. Future research should explore adaptive perforations, machine learning optimization, hybrid structures, and acoustic metamaterial integration.